Environmental information disclosure and total factor productivity in China’s enterprises - Changhua Chen; Yuqing Luo; Junbing Huang (Energy Strategy Reviews)
Environmental Information Disclosure (EID) stands as a pivotal initiative in advancing environmental management strategies. Leveraging China’s 2015 Environmental Protection Law as a quasi-natural experiment, this paper employs the difference-in-differences (DID) method to delve into the impact of EID on enterprises’ Total Factor Productivity (TFP) based on a panel dataset of Chinese listed enterprises from 2009 to 2020. To further unravel the underlying mechanisms, a two-step analytical approach is undertaken. The key findings unequivocally reveal that EID positively and consistently contributes to the enhancement of TFP, with more pronounced positive effect on large state-owned enterprises and those located in provincial capital cities or municipalities. For the influencing channels, results demonstrate that EID prompts enterprises to embark on green mergers and acquisitions (GMA), facilitating access to cutting-edge green technologies and growth. Furthermore, the estimates also reveal that external support can effectively alleviate financing constraints faced by enterprises. These findings underscore GMA’s role in sustainable development and beneficial in carrying out insightful policy implications.